Muscle plays a more superior role than fat in bone homeostasis: A cross-sectional study of old Asian people - Liu, Chaoran; Wong, Pui Yan; Tong, Xin; Chow, Simon Kwoon-Ho; Hung, Vivian Wing-Yin; Cheung, Wing-Hoi; Qin, Ling; Law, Sheung Wai; Wong, Ronald Man Yeung (Frontiers in Endocrinology, 2023)
Objectives: To discover the role of fat and muscle in bone structures, as well as the relationship between obesity and sarcopenia on age-related osteoporosis. Methods: A total of 400 participants (65.0 ± 8.2 years old, 42.3% female) were recruited. Fat, muscle, bone parameters, basic demographics, medical history, physical performance and activity, calcium intake of participants were obtained from datasets. The diagnosis of osteoporosis, sarcopenia, and obesity was based on current recommendations. Pearson correlation, non-linear regression models, and decision tree analyses were performed to study the relationship between fat, muscle, and bone. Logistic regression analyses were used to explore the risk of osteoporosis in old people with obesity or sarcopenia via Model 1 (unadjusted) and Model 2 (adjusted by age, physical activity, and calcium intake). Results: Correlation analysis showed limb muscle mass and index, and age were best related to bone mineral density (BMD) (|r|=0.386–0.632, p<0.001). On the contrary of body mass index (BMI), increased body fat percentage (BF%) were harmful for bone health. An increase of BMI and fat mass index slowed the increase of BMD in the spine, whilst skeletal muscle mass index accelerated the increase. People with sarcopenia had low muscle mass and strength. When separating subjects into sarcopenia and non-sarcopenia status, sarcopenia was independently related to higher risks of osteoporosis in both models (OR>1, p<0.05). BMI-defined obesity in Model 1, as well as BF%-defined obesity in both models did not reduce the risk of osteoporosis in both models (p>0.05). The decision tree classification (85% accuracy) showed greater body weight and larger lower limb muscle performance were negatively related to osteoporosis, whilst fat mass and percentage did not play roles in this prediction. Conclusion: Low muscle mass and function were harmful to bone health. Obesity defined by both BMI and BF% had limited protective roles in osteoporosis. The benefits for bone from increased muscle mass and function plays a more superior role than increased fat mass in old people. Sarcopenia prevention and treatment instead of controlling obesity should be recommended as an approach to reduce the risks of age-related osteoporosis and fragility fracture for elderly people.